The Role of Moderating Economic Growth Variables on the Effect of Allocation Funds and Capital Expenditures in Local Government - Eddy Sarwono, Aris; Saptantinah Puji Astuti, Dewi (CV. Inara, 2021)
This study aims to analyze the effect of the General Allocation Fund (DAU) and Special Allocation Fund (DAK) variables on capital expenditures. In addition, this study uses the role of intervening variables to analyze the effect of these variables. The data source for this research uses secondary data sources originating from the Director General of Fiscal Balance of the Regional Government. Respondents in this study were local governments in Central Java with a total of 35 regencies and cities for the period 2016-2019. The results of the analysis show that the DAU variable has a positive and significant effect on capital expenditure while the DAK variable has no significant effect on the modal expenditure variable. In addition, the results of the analysis also show that the variable Economic Growth (PE) is not a variable that mediates the effect of DAU on capital expenditure, while further analysis shows that PE is a variable that mediates the effect of DAK on capital expenditure.